The effect of deep brain stimulation on motor functions and quality of life in the treatment of dystonia (Annals of Medical Research, 2023)
Aim: The present research aims to investigate the levels of depression and health-related quality of life (HRQoL) after surgical globus pallidus internus deep brain stimulation (Gpi-DBS) treatment in patients with generalized dystonia and segmental dystonia refractory to medical treatment.Materials and Methods: Seventeen patients diagnosed with primary and secondary dystonia who were selected for GPi-DBS by the neurology, neurosurgery, and psychiatry council were included in the study. The patients were studied in two groups: primary dystonia and secondary dystonia. The Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS) was used to assess dystonia-related loss of function and disability, the Short Form 36 (SF-36) to assess HRQoL levels, and the Beck Depression Inventory (BDI) to assess depression levels in all patients before Gpi-DBS and 1 year after Gpi-DBS, retrospectively.Results: In this study, significant improvement in BFMDRS scores and significant improvement in HRQoL levels were observed after 1 year of Gpi-DBS treatment in all dystonia types. Moreover, significant improvement was found in dystonia severity and disability levels, and HRQoL levels in the primary and secondary dystonia subgroups.Conclusions: The study suggests that Gpi-DBS improves dystonia symptoms, and increases HRQoL levels in dystonia. In addition, this study is the first in Turkey to investigate the effect of Gpi-DBS on HRQoL levels in dystonia. However, we believe that further research with more participants is also needed in Turkey in this regard.
Keywords: Dystonia; Gpi-DBS; Health-related quality of life